Revisiting the gut–joint axis: links between gut inflammation and spondyloarthritis - Gracey, Eric; Vereecke, Lars; McGovern, Dermot; Fröhling, Mareike; Schett, Georg; Danese, Silvio; De Vos, Martine; Van den Bosch, Filip; Elewaut, Dirk (Nature Reviews Rheumatology, 2020)
Gut inflammation is strongly associated with spondyloarthritis (SpA), as exemplified by the high prevalence of inflammatory bowel disease (IBD) and the even higher occurrence of subclinical gut inflammation in patients with SpA. The gut–joint axis of inflammation in SpA is further reinforced by similarities in immunopathogenesis at both anatomical sites and by the clinical success of therapies blocking TNF and IL-23 in IBD and in some forms of SpA. Many genetic risk factors are shared between SpA and IBD, and changes in the composition of gut microbiota are seen in both diseases. Current dogma is that inflammation in SpA initiates in the gut and leads to joint inflammation; however, although conceptually attractive, some research does not support this causal relationship. For example, therapies targeting IL-17A are efficacious in the joint but not the gut, and interfering with gut trafficking by targeting molecules such as α4β7 in IBD can lead to onset or flares of SpA. Several important knowledge gaps remain that must be addressed in future studies. Determining the true nature of the gut–joint axis has real-world implications for the treatment of patients with co-incident IBD and SpA and for the repurposing of therapeutics from one disease to the other.
CRIS-Team Scopus Importer:2020-07-24